2019
DOI: 10.9775/kausbed.2018.026
|View full text |Cite
|
Sign up to set email alerts
|

Albert Camus and Ideology Criticism

Abstract: Başta iki büyük savaş olmak üzere, soğuk savaş yıllarının derin ideolojik çatışmaları içerisinde Albert Camus insanı ezen her türden totaliter yönelimler ve yönetimlerin karşısındadır. Hayır diyebilen insan olarak tanımlamaya çalıştığı "başkaldıran insan" kavramını öncelikle özgürlük ekseninde somutlaştırır. Bu kapsamda Fransız ahlak ve vicdanından başlayıp çağın Avrupa'sının değerler sistemini içine alacak şekilde, insan bilincini kurcalayabilecek her sorunun derin köklerine iner ve yapıtının izleksel önceliğ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 0 publications
0
2
0
6
Order By: Relevance
“…Thus, this result of the current study focused on the vocational high school students' English-speaking anxiety complies with the result reported by Kozikoğlu (2018), who investigated the extent to which the high school students' English speaking anxiety and attitudes towards English predicted their level of participation in lessons. However, Yılmaz (2019), who aimed to reveal the English-speaking anxiety levels of high school students together with its accompanying reasons, concluded that the 10 th grade students have a higher level of English speaking anxiety than the 9 th and 11 th grade students. This finding contradicts with the finding of the current study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, this result of the current study focused on the vocational high school students' English-speaking anxiety complies with the result reported by Kozikoğlu (2018), who investigated the extent to which the high school students' English speaking anxiety and attitudes towards English predicted their level of participation in lessons. However, Yılmaz (2019), who aimed to reveal the English-speaking anxiety levels of high school students together with its accompanying reasons, concluded that the 10 th grade students have a higher level of English speaking anxiety than the 9 th and 11 th grade students. This finding contradicts with the finding of the current study.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the main causes of foreign language speaking anxiety were determined as fear of making mistakes (especially pronunciation mistakes), lack of vocabulary and the teacher's attitudes. Yılmaz (2019) examined the causes of high school students' anxiety about speaking the foreign language in English lessons in relation to different variables. In the study, no significant difference was observed as a result of the implementation of the English-speaking anxiety scale.…”
Section: International Journal Of Languages' Education and Teachingmentioning
confidence: 99%
“…Genel anlamda okuduğunu anlama, bir metinde yer alan fikirlerin bulunması ve anlamlandırılması olarak ifade edilebilir (Yılmaz 2008). Güneş (2004) tarafından okuduğunu anlama, metinde okuyucuya verilmek istenen anlamın bulunması, anlam üzerine fikir yürütme, neden sonuç ilişkisini sorgulama, ulaşılan sonuçların değerlendirilmesi olarak ifade edilmiştir.…”
Section: Introductionunclassified
“…Gerek basılı gerekse çevrim içi bir ortamda gerçekleştirilebilen okuma becerisi; bir dizi değişkenden etkilenebilen çok yönlü, karmaşık zihinsel bir aktivitedir. Ön bilgi (Yılmaz, 2014;Uyar, 2015), motivasyon (Yıldız ve Akyol, 2011), tutum (Boz ve Ulusoy, 2020), kaygı (Türkben, 2020), öz yeterlik (Sur ve Ateş, 2022), kelime dağarcığı (Kavcar ve Kantemir, 1986), strateji kullanımı (Ergen ve Batmaz, 2019), sosyoekonomik yapı (Sur, 2022) okuma başarısını etkileyen değişkenler arasında yer almaktadır. Okuma başarısını etkileyen birçok değişken olmakla birlikte alanyazın, motivasyonun okuduğunu anlama becerisi üzerinde kritik öneme sahip olduğunu göstermektedir.…”
Section: Introductionunclassified